Treatment of paint wastewater by using Tacca Leontopetaloides starchas a natural coagulant and Calcium Oxide as a coagulant aid: article - Mohd Nasir, Nur Farah Yumni; Ku Hamid, Ku Halim (2017)
The research works involve the study of effectiveness of Tacca Leontopetaloides starch as a natural coagulant and Calcium Oxide and as its coagulant aid for the treatment of paint wastewater. Three main parameters were studied; chemical oxygen demand (COD), turbidity and heavy metals removal of effluent. Coagulation treatment using jar test were performed with a flocculation system where the effects of paint wastewater pH as well as Tacca Leontopetaloides starch dosage on coagulation effectiveness were probed. The highest record of COD and turbidity removal percentage were 95% and 60% respectively, observed for effluent at optimum pH 7 using 90 mL dosage. The metals concentration after treatment also showed significant removal which complied with Standard B of Environmental Quality (Industrial Effluent) Regulations 2009 stipulated by the Department of Environment (DOE), Malaysia. It could be conclude that Tacca Leontopetaloides starch showed great potential as a natural coagulant for water treatment purposes and could be applied in the pre-treatment stage of Malaysian paint wastewater prior to secondary treatment.